Understanding the significance of Staphylococcus epidermidis bacteremia in babies and children - Cheung, Gordon Y C (2010)
PURPOSE OF REVIEW: This review provides an overview of Staphylococcus epidermidis bacteremia/sepsis and Coagulase-negative staphylococci (CoNS) infections in neonates and children. RECENT FINDINGS: The incidence of S. epidermidis and CoNS sepsis in neonates is still very high and preventing and treating disease remains difficult. There has been recent progress in understanding pathogenesis of S. epidermidis infection, interaction of S. epidermidis with host defenses, and risk factors for the development of S. epidermidis disease. For example, we have gained more insight into the development of biofilm-associated catheter infections, which are responsible for recurrent CoNS infections in hospitalized premature neonates and are especially difficult to treat owing to intrinsic resistance of biofilms to antibiotics. SUMMARY: Biofilm-associated catheter infections by S. epidermidis occur frequently in neonates and adults. S. epidermidis bloodstream infections are particularly problematic in neonates. Prophylaxis in the form of eradicating colonizing S. epidermidis may be a double-edged sword, as S. epidermidis colonization may be beneficial to the host. New drugs may arise from a better understanding of S. epidermidis virulence and analysis of risk factors may help identify neonates susceptible to bacterial sepsis. However, reducing morbidity should always begin by increasing hygiene in hospital settings to reduce the introduction of potentially harmful opportunistic pathogens such as S. epidermidis on indwelling medical devices or during surgery.